Sustainability of Scientific Buffalo Husbandry Practices in Bihar and Haryana - Yadav, V. K.; Jha, S.K; Vijay, Tuhina; Supriya, P. (Indian Journal of Extension Education, 2012)
The present study was conducted in two purposively selected States, i.e. Bihar and Haryana, in order to compare the  degree of perceived sustainability of scientific buffalo husbandry practices and to ascertain the perceptual differences  among the experts and dairy farmers regarding various dimensions of sustainability. A total sample size of 160 dairy  farmer respondents and 40 Subject Matter Specialist (SMS)/ Experts were selected. Data were collected by using personal  interview method. The collected data were tabulated, analysed and interpreted with the help of appropriate statistical  tools. Sustainability scores with respect to artificial insemination (A.I.), feeding green fodder, vaccination and deworming  in buffalo obtained from both farmer and expert respondents were found to be more in Haryana than Bihar. The experts  perceived significantly higher sustainability of practices in both States. There is a need to improve the A.I. services,  marketing of green fodder and dissemination of technical know-how of vaccination and deworming.
Keywords: Artificial insemination buffalo; deworming (dew); green fodder; sustainability; vaccination